Transforming heavy equipment engineering learning using virtual reality: A literature review and case study - Chamdan Nor Ihwan Tsauri; Putu Sudira; Muhammad Irfan Luthfi (Jurnal Pendidikan Vokasi, 2024)
The transformation of education in Indonesia is influenced by the development of digital technology. Over time, the world of education in Indonesia is able to transform to keep up with developments in the digital era. One form of transformation is learning through virtual reality media. This research aims to explore the impact of virtual reality transformation on learning heavy equipment engineering. The research methods used in this research are case studies and literature. A quantitative approach through quasi-experimental research with a post-test only control group design, was also used to gain a deeper understanding of the impact of virtual reality on learning outcomes. The data obtained was analysed using descriptive methods, qualitative data was analysed using qualitative descriptive, and quantitative data was analysed using quantitative descriptive. The results of the analysis show that learning transformation is needed so that it can be carried out properly in accordance with various environmental conditions. The use of virtual reality in learning heavy equipment engineering encourages digital learning transformation to improve the quality of learning through simulation of practical learning. The use of virtual reality in learning heavy equipment engineering can improve student understanding, although virtual reality transformation cannot fully replace the role of conventional learning because there are some competencies that must be taught directly. Although this research is exploratory, the empirical insights gained can make a valuable contribution as a reference for the development of virtual reality-based learning.